Comparison of neosaxitoxin versus bupivacaine via port infiltration for postoperative analgesia following laparoscopic cholecystectomy: a randomized, double-blind trial - Rodríguez-Navarro, Alberto J; Berde, Charles B; Wiedmaier, Gonzalo; Mercado, Andres; Garcia, Carlos; Iglesias, Veronica; Zurakowski, David (Regional anesthesia and pain medicine, 2011)
Wound infiltration with available local anesthetics generally provides analgesia for less than 8 hrs. The site 1 sodium-channel toxin neosaxitoxin (neoSTX) produced analgesia for over 24 hrs in animals and human volunteers. In this randomized, double-blind trial, we examined the postoperative course of patients undergoing laparoscopic cholecystectomy under a standardized general anesthesia with wound infiltration using either neoSTX or bupivacaine. We hypothesized that neoSTX would reduce pain compared with bupivacaine at 12 hrs postoperatively. Patients received preincisional infiltration of laparoscope entry sites with 20 mL containing either neoSTX (total dose, 100 μg) or bupivacaine 0.25% (total dose, 50 mg). The primary outcome measure was the visual analog pain score at 12 hrs postoperatively. Secondary outcomes included repeated pain scores at rest and with movement,analgesic use, functional recovery, and adverse effects. Groups were compared using Mann-Whitney U tests for pain scores, Fisher exact test for proportions of patients with severe pain and complete analgesia, and Kaplan-Meier curves for time to full recovery. Among 137 subjects, 69 were randomized to neoSTX and 68 to bupivacaine. Median pain scores at rest and with movement 12 hrs postoperatively were lower in the neoSTX group compared with the bupivacaine group (P<0.01). Additional pain measures and recovery parameters also favored neoSTX. No serious adverse events occurred,and no adverse events were more frequent in the neoSTX group. NeoSTX shows promise as a long-acting local anesthetic. Future studies will examine dose response, combination formulations, and safety with dose escalation.